2021
DOI: 10.1186/s12893-021-01371-4
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal hernia repair in inpatient children: a nationwide analysis of German administrative data

Abstract: Background Contrary to adult inguinal hernia surgery, large-scale investigations using registries or administrative data are missing in paediatric surgery. We aimed to fill this gap by analysing German administrative hospital data to describe the current reality of inpatient hernia surgery in children. Methods We analysed aggregated data files bought from the German federals statistics office on hospital reimbursement data separately for principal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, there seems to be a trend towards more prevalent utilization of the laparoscopic technique. In a study of German administrative claims data for the years 2005-2017, laparoscopic IHR was used in boys for between 1% and 3% of cases and in girls for between 2% and 14% of cases for the different age groups [19]. While our analysis showed that the open technique is still used in more than 90% of all patients in 2019, the percentage of laparoscopic IHR increased to 6% of boys and 17% of girls.…”
Section: Discussionmentioning
confidence: 59%
“…However, there seems to be a trend towards more prevalent utilization of the laparoscopic technique. In a study of German administrative claims data for the years 2005-2017, laparoscopic IHR was used in boys for between 1% and 3% of cases and in girls for between 2% and 14% of cases for the different age groups [19]. While our analysis showed that the open technique is still used in more than 90% of all patients in 2019, the percentage of laparoscopic IHR increased to 6% of boys and 17% of girls.…”
Section: Discussionmentioning
confidence: 59%
“…Statistical analyses were conducted using R (RRID: SCR_001905) (version 3.5.3) with its generic stats4 package [9], if not stated otherwise. Changes over time were analysed by ordinary least squares linear regression [10][11][12][13], whose requirements of normality of residuals were checked by using the Kolmogorov-Smirnov test and the presence of homoscedasticity was verified by the Breusch-Pagan test, both from the olsrr package (version 0.5.3) [14], aided by visual analysis of QQ plots [15].…”
Section: Open Accessmentioning
confidence: 99%